A comparative study of the catalytic performance of nickel supported on a hibonite-type La-hexaaluminate synthesized from aluminum saline slags in the dry reforming of methane. (1st December 2022) - Torrez-Herrera, J.J.; Korili, S.A.; Gil, A.
Abstract: In this work, a hibonite-type Ni/La-hexaaluminate (Ni/LHA) synthesized from an industrial waste is used and compared as catalyst in the dry reforming of methane (DRM) at 973 K. The structure, catalytic behavior, and stability during a run time of at least 50 h of three Ni-catalysts obtained from two commercial supports and two preparation methods were used for comparison. An aluminum solution (9.40 g/L) obtained from an aluminum saline slag waste by acid extraction was used to synthesize the hexaaluminate by mixing with a stoichiometric amount of lanthanum nitrate and methanol/Peg400/PegMn400 under hydrothermal conditions at 493 K for 16 h. The Ni/LHA catalyst (10 wt% NiO) was obtained by impregnation of the synthesized support, calcined previously at 1473 K for 2 h. The resulting solids were characterized by several techniques as: X-ray diffraction (XRD), N2 adsorption at 77 K, temperature-programmed reduction (TPR), scanning electron microscopy (SEM) and transmission electron microscopy (HR-TEM). In order to compare the catalytic behavior and properties of the Ni/LHA catalyst, three Ni catalysts obtained from two commercial supports (γ-Al2 O3 and SiO2 ) and two preparation methods (wet impregnation (I) and precipitation-deposition (PD)) were synthesized. Analysis of the TPR patterns for the catalysts allowed the type of metal support interaction and NiO species to be determined, with a weak interaction with the support being observed in Ni/LHA and Ni–I/SiO2 . The NiO species observed, with crystallite sizes between 9.7 and 40.4 nm, confirm the X-ray structural analyses. The Ni/LHA catalyst was found to be active and very stable in the DRM reaction after 50 h. The catalytic behavior was evaluated from the CO2 and CH4 conversions, as well as the H2 /CO selectivity, with values of 99% over almost all the time range evaluated. The behavior of this catalyst is comparable to that of Ni–I/Al2 O3 and Ni-PD/SiO2 . The results found indicating that the strong interaction of nickel with the support favors the stability of the catalysts in the DRM reaction. Highlights: Acid aluminum extracted was used in the synthesis of a La-hexaaluminate. The solid was used as support for Ni catalyst for DRM. Three Ni-catalysts from commercial supports were used for comparison. The behavior of Ni/LHA is similar to the catalysts with high Ni-support interaction.